2021
DOI: 10.3389/fimmu.2021.641696
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Potential of Fruits and Their Extracts in Poultry

Abstract: The impact of antibiotic use for growth promotion in livestock and poultry production on the rise of antimicrobial resistance (AMR) in bacteria led to the ban of this practice in the European Union in 2006 and a restriction of antimicrobial use (AMU) in animal agriculture in Canada and the United States of America. There is a high risk of infectious diseases such as necrotic enteritis due to Clostridium perfringens, and colibacillosis due to avian pathogenic Escherichia coli in antimicrobial-free broiler chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 84 publications
1
24
0
1
Order By: Relevance
“…The immune regulation on a transcriptional level was not considerably impaired in the GGP- and WYC-fed broilers. These results are in accordance with the observations of Hasted et al [ 32 ] where the majority of trials supplementing polyphenols in broilers diet had no effect on immune status. However, a suppression of the mRNA levels of the pro-inflammatory mediators would be expectable and desirable due to the high proportion of epicatechin [ 48 , 49 ] and b-glucans [ 50 ] in the GGP and WYC groups, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The immune regulation on a transcriptional level was not considerably impaired in the GGP- and WYC-fed broilers. These results are in accordance with the observations of Hasted et al [ 32 ] where the majority of trials supplementing polyphenols in broilers diet had no effect on immune status. However, a suppression of the mRNA levels of the pro-inflammatory mediators would be expectable and desirable due to the high proportion of epicatechin [ 48 , 49 ] and b-glucans [ 50 ] in the GGP and WYC groups, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have trumpeted the immune-enhancing properties of grape pomace based only on a positive response in the IgM in the primary titer of broilers fed with grape pomace [ 30 , 31 ]. Notably, Hasted et al [ 32 ] summarized eleven studies focused on the effect of grape byproducts on poultry immunity. Interestingly, 9 out of 11 studies did not observe any effect on immune regulation, 2 out of 11 demonstrated a significant improvement in antibody levels, while there were no data about their effect on the pro-inflammatory regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Total anthocyanin concentration was estimated using pH differential protocol [32] as described in Wu et al [33]. The absorbance (Ab) was calculated by Equation (1).…”
Section: Determination Of Bioactive Compounds In Anthocyanin-rich Ros...mentioning
confidence: 99%
“…Recent poultry feeds are manufactured to satisfy their nutritional needs. Still, more research is required to determine whether these feeds sufficiently maintain the birds' immunity system or if additional components are needed to enhance their immune function [1]. Furthermore, the growth performance improvements in broiler chickens are associated with intestinal health [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Poultry meat has become the most consumed and affordable type of meat among animal sources, worldwide [2]. By 2026, poultry meat is expected to account for 45% of global meat consumption [3]. In recent years, with improvements in living standards, people have begun to pay more attention to meat quality.…”
Section: Introductionmentioning
confidence: 99%